Extracapsular spread in oral squamous cell carcinoma and its association with GGH, CDKN3 and CBX7 - Burhanudin, Nor Aszlitah; Kallarakkal, Thomas George (2018)
PURPOSE OF STUDY: Extracapsular spread (ECS) in oral squamous cell carcinoma (OSCC) indicates tumour aggressiveness and is associated with a higher risk for tumour recurrence, loco-regional spread and distant metastasis. The identification of specific biomarkers that could predict ECS would guide the clinicians in the management of OSCC patients. This study aimed to determine the association between clinical and pathological parameters of OSCC patients with ECS. We also sought to investigate the expression of Gamma Glutamyl Hydrolase (GGH), Cyclin Dependent Kinase Inhibitor 3 (CDKN3) and Chromobox Homolog 7(CBX7) and their potential use as biomarkers to predict ECS in OSCC. MATERIALS AND METHODS: Association between clinicopathological parameters and expression of these markers with ECS status was analysed using chi-square test. Immunohistochemical staining with anti-GGH, anti-CDKN3 and anti-CBX7 antibodies was performed on 35 OSCC cases. RESULTS: The number of positive nodes and the highest anatomical level of nodal involvement significantly correlated with ECS (p<0.05). Immunohistochemical staining results indicated that high GGH expression was significantly associated with ECS (p<0.05), while no significant association was seen for CDKN3 and CBX7 expression with ECS. However, a trend towards significance was observed with a high level of CDKN3 and low level of CBX7 expression with ECS. CONCLUSIONS: The presence of ECS is a predictor for the pathological involvement of greater number of nodes from a higher anatomical level. GGH offers potential as a prognostic biomarker in OSCC, while the role of CDKN3 and CBX7 as prognostic markers need to be validated in a larger sample.